FAILURE ANALYSIS OF AUTO SEAT BACKREST ADJUSTER BASED ON GTN MODEL - HAN JinHui; WANG JianWei (Jixie qiangdu)
Aiming at the failure phenomenon of auto seat backrest adjuster under limiting operational condition, the finite element model is established to obtain the stress field and deformation field of all parts. And this work can provide guidance for the structural optimization design. The constitutive relationship law of all parts of seat backrest adjuster can be described well by elastic-plastic model and GTN model. By using the different flow stress models and damage parameters, the mechanic parameters of material which were in good agreement with the result of uniaxial tension test is obtained. On this basis, simulation of seat backrest adjuster is presented by the explicit dynamics method. The results show that fault shearing zones can be found at the boss root of chute. The present method can provide the guidance of structural strength check.